Causes of Poor Performance in English at Secondary School Level in Pakistan - Zubair Khan (University of Chitral Journal of Linguistics and Literature, 2023)
This qualitative study explored causes of poor performance of students in English language at secondary schoollevel. The sample of the study consisted of 31 teachers of English,teaching in public sector schools in Abbottabad, Pakistan.Data was collected using semi-structured interviews and was analysed using thematic analysis. Findings revealed that lack of adequate administration, lack of facilities, inadequate examination system, large class size, under qualified teachers, inadequate language teaching methods, and lack of cooperation on the part of parents were major causes of poor performance ofstudents in English language at secondary level. The study has important implications for teachers, students, policy makers and education researchers.